Estudo do impacto da contagem de micropartículas na doença do enxerto contra o hospedeiro - Carneiro, Thiago Xavier [UNIFESP] (2016)
Graft-versus-host disease (GvHD) remains a leading cause of morbidity and mortality among allogeneic stem cell transplantation (SCT) patients. New research focusing on diagnostic methods and therapeutic interventions is needed. Microparticles (MPs) have been described as biomarkers of cellular damage, activation, and intercellular signaling in many diseases. This study examined the correlations of the levels of MPs with the incidence of acute GvHD. Circulating annexin V-positive (total microparticles - TMP), CD61+ platelet-derived microparticles (PMP) and CD235+ erythrocyte-derived microparticles (EMP) were measured at neutrophil engraftment in the plasma of 48 patients undergoing SCT. The levels of PMP were not associated with the risk of acute GvHD. However, higher TMP count (above 520/?L) and higher EMP count (above 360/?L) were associated with a greater incidence of acute GvHD (54% vs. 21%, p=0.02 and 59% vs. 26%, p=0.04, respectively) p=0.02). In patients exposed to reduced intensity conditioning regimens, an even stronger association of high TMP and EMP count and acute GvHD was observed (77% vs. 22%, p=0.003 and 89% vs. 23%, p=0.002, respectively). Our data suggest that higher total microparticles and erythrocyte derived microparticles counts at engraftment may be associated with a greater risk of acute GvHD.